(3Odjd GdWGdH dfjd GdeWGdHs - (3GdcQej, eQYj Hf jhSa Hf CHj HcQ, J (B1023 (3g`s ((3GdeOQSI GdeQGOjIs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO agPG eNJUQ aj Gdabg Ydi GdePgH GdCMeO ePgH GdEeGe CMeO hSejJg Odjd GdWGdH dfjd GdeWGdH cJGH GdWgGQI hgj OaY GdMOK hPG GdNHK hCbSGe GdeGA KdGKI s
(3BNQgG (B:s
(3hdh cPHhg hjMce HESdGe ef CbQ hdh eejRG bHjd ehJg TgGOI Cf dG Edjg EdG Gddg hCf eMeOG QShd Gddg Gddge GLYdfj eef CbQ HgG eNdUG aj MjGJg hYfO hHLfGf GdfYjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 203s
(3eYLe GdeDdajf (B3 / 842s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3Gdabg GdMfHdjs